(untitled) (Marketing Journal, 2025)
This article presents an in-depth analysis of international experiences in econometric modeling of labor resource dynamics , with a special focus on the impact of the global pandemic and economic shocks on the development of the international labor market. The study provides scientific evidence that economic instability during 79 the pandemic adversely affected labor market stability . Key structural issues such as rising youth unemployment , the expansion of underemployment , increased informal employment , and inequalities in employment based on gender and skill levels have been identified . Each of these issues has been empirically analyzed through economic models and illustrated with practical examples from various countries . The findings underscore the importance of assessing labor market flexibility during global crises such as the pandemic and formulating effective policy responses .